Lipid Lowering Therapy and Stabilization of Atherosclerotic Plaques - Krone, Wilhelm; Müller-Wieland, Dirk (Thrombosis and Haemostasis, 1999)
Lipid-lowering therapy leads to a great reduction of cardiovascular complications, but has almost no effect on the degree of stenosis of coronary arteries. These and other studies have lead to a new paradigm of coronary artery disease, i. e. clinical prognosis is not only determined by the extent of a single stenosis, but mainly by the number and structure of atherosclerotic plaques. Rupture of an instable or vulnerable plaque, characterized by a large lipid-rich central core, inflammatory cells, and a thin fibrous cap, causes sudden thrombus formation and thereby acute coronary syndromes. There is accumulating evidence that cholesterol lowering can result in plaque stabilization and improvement of endothelial dysfunction.
Keywords: Lipid lowering therapy; plaque stabilisation